Patient, surgical and hospital factors associated with the presence of a consultant surgeon during hip fracture surgery. Do we know the answer?. Issue 7 (20th April 2021) - Fajardo Pulido, Diana; Ryder, Tayhla; Harris, Ian A.; Close, Jaqueline C. T.; Chehade, Mellick J.; Seymour, Hannah; Harris, Roger; Armstrong, Elizabeth; Mitchell, Rebecca
Abstract: Background: Provision of quality care can help to reduce adverse health outcomes following hip fracture. While surgical management by either a consultant or junior surgeon has shown inconclusive differences in patient outcomes, consultant presence is often recommended, yet little is known about the factors that influence whether a consultant surgeon is present during hip fracture surgery. The aim of this study is to examine patient, surgical and hospital factors associated with having a consultant surgeon present during hip fracture surgery. Methods: An examination of hip fracture surgeries of adults aged ≥ 50 years admitted to hospitals in Australia and New Zealand between 1 January 2015 and 31 December 2018 using data from the Australia and New Zealand Hip Fracture Registry was conducted. Multivariable logistic regression was used to examine factors associated with the presence of a consultant surgeon during hip fracture surgery. Results: There were 29 530 hip fracture surgeries 58.1% had a consultant surgeon present (range 8.5–100% by hospital). Patients were more likely to have a consultant surgeon present during surgery if they had private health insurance, were operated on after hours, required total hip replacements or were operated on in hospitals that conducted ≤150 surgeries per year. Conclusion: There is variation in the presence of consultant surgeons within Australia and New Zealand during hip fracture surgery, potentially associated with the complexity of surgery and hospital factors. However, further research is needed to determine the optimum level of supervision required based on patient factors and surgical complexity. Abstract : The study reports on patient, surgical and hospital factors associated with the presence of a consultant surgeon during hip fracture surgery. It describes variation in the presence of a consultant surgeon influenced by the complexity of hip fracture surgery and hospital volume. Potentially, operating times for patients with specific surgical characteristics could be allocated within surgical teams.